Evaluating HbA1c as a Predictive Biomarker for Depression in the Elderly: A Cross-Sectional Analysis - Wijaya, Bryan Anna; Gunawan, Shirly; Firmansyah, Yohanes (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Introduction: Depression in the elderly is a significant public health concern and is linked to elevated HbA1c, a marker of long-term glucose control. Persistent hyperglycemia may impair neurogenesis, disrupt brain networks, and reduce neurotransmitter activity, making HbA1c a potential biomarker for depression. Purpose: This study aims to explore the potential of HbA1c as a biomarker for predicting depression severity in the elderly. Methods: This cross-sectional study examined 93 elderly residents at Bina Bhakti Nursing Home, who exhibited varying levels of depression severity. Depression was assessed using the Geriatric Depression Scale (GDS), and HbA1c levels were analyzed using an automated clinical analyzer. To evaluate the predictive ability of HbA1c for depression severity, we used the area under the curve (AUC) from a receiver operating characteristic (ROC) analysis. A GDS score of 4 or higher was used to indicate severe depression. Results: The AUC for HbA1c was 0.692, with a p-value of 0.049, indicating a statistically significant relationship between HbA1c levels and depression severity. Conclusion: Elevated HbA1c levels may serve as a potential biomarker for depression risk in the elderly. Routine HbA1c monitoring could support early detection and timely intervention. Further research is needed to clarify its clinical relevance.